Investigation of the evolution of radiation-induced lung damage using serial CT imaging and pulmonary function tests. (July 2020) - Veiga, Catarina; Chandy, Edward; Jacob, Joseph; Yip, Natalie; Szmul, Adam; Landau, David; McClelland, Jamie R.
Highlights: Detailed RILD evolution described by objective radiological and pulmonary function measures. RILD is associated with volume loss of the treated lung and contralateral lung hyperinflation. Objective radiological findings might differentiate subjects with early versus late RILD. Most patients developed progressive lung damage, even when the early phase is absent/mild. Pre-RT lung function and RT dosimetry may identify subjects at increased risk of developing RILD. Abstract: Background and purpose: Radiation-induced lung damage (RILD) is a common consequence of lung cancer radiotherapy (RT) with unclear evolution over time. We quantify radiological RILD longitudinally and correlate it with dosimetry and respiratory morbidity. Materials and methods: CTs were available pre-RT and at 3, 6, 12 and 24-months post-RT for forty-five subjects enrolled in a phase 1/2 clinical trial of isotoxic, dose-escalated chemoradiotherapy for locally advanced non-small cell lung cancer. Fifteen CT-based measures of parenchymal, pleural and lung volume change, and anatomical distortions, were calculated. Respiratory morbidity was assessed with the Medical Research Council (MRC) dyspnoea score and spirometric pulmonary function tests (PFTs): FVC, FEV1, FEV1 /FVC and DLCO. Results: FEV1, FEV1 /FVC and MRC scores progressively declined post-RT; FVC decreased by 6-months before partially recovering. Radiologically, an early phase (3–6 months) of acute inflammation was characterised by reversible parenchymal change and non-progressive anatomical distortion. A phase of chronic scarring followed (6–24 months) with irreversible parenchymal change, progressive volume loss and anatomical distortion. Post-RT increase in contralateral lung volume was common. Normal lung volume shrinkage correlated longitudinally with mean lung dose ( r  = 0.30–0.40, p  = 0.01–0.04). Radiological findings allowed separation of patients with predominant acute versus chronic RILD; subjects with predominantly chronic RILD had poorer pre-RT lung function. Conclusions: CT-based measures enable detailed quantification of the longitudinal evolution of RILD. The majority of patients developed progressive lung damage, even when the early phase was absent or mild. Pre-RT lung function and RT dosimetry may allow to identify subjects at increased risk of RILD.